Meta-Analisis Validitas Media Pembelajaran Komik Digital pada Pembelajaran Biologi: (Meta-Analysis of the Validity of Digital Comics Learning Media on Biology Learning) - Anggraini, Berlian; Zulyusri, Zulyusri (BIODIK, 2023)
The development of information and communication technology requires education to help students adapt by mastering various skills to succeed in the learning process. Learning media can be interpreted as a forum for delivering messages containing learning materials so that the goals of the learning process are achieved. Digital comics function as well as a visual communication tool between students and teachers in delivering learning materials. Data collection is carried out by reviewing and analyzing articles from journals related to digital comic learning media. The samples used were 10 journals related to the development of digital comic learning media. The results of the research meta-analysis were for digital comics learning media obtained and average score of 87,56% with a very valid category. abstrak. Perkembangan teknologi informasi dan komunikasi menuntut pendidikan untuk membantu peserta didik beradaptasi dengan menguasai berbagai keterampilan agar berhasil dalam proses pembelajaran. Media pembelajaran bisa diartikan sebagai wadah penyampai pesan yang berisi materi pembelajaran sehingga tujuan dari peroses pembelajaran tercapai. . Komik digital difungsikan dengan baik sebagai alat komunikasi visual antara peserta didik dan pendidik dalam menyampaikan materi pembelajaran. . Pengumpulan data dilakukan dengan mengkaji dan menganalisis artikel-artikel dari jurnal yang berhubungan dengan media pembelajaran komik digital. Sampel yang digunakan adalah 10 jurnal yang berkaitan dengan pengembangan media pembelajaran komik digital. Hasil meta-analisis penelitian adalah untuk media pembelajaran komik digital didapatkan rata-rata nilai sebesar 87,56% dengan kategori sangat valid.